Ketogenic interventions in mild cognitive impairment, Alzheimer's disease, and Parkinson's disease: A systematic review and critical appraisal - Bohnen, Jeffrey L. B.; Albin, Roger L.; Bohnen, Nicolaas I. (Frontiers in Neurology, 2023)
Background There is increasing interest in therapeutic ketosis as a potential therapy for neurodegenerative disorders–in particular, mild cognitive impairment (MCI), Alzheimer's disease (AD), and Parkinson's disease (PD)–following a proof-of-concept study in Parkinson's disease published in 2005. Methods To provide an objective assessment of emerging clinical evidence and targeted recommendations for future research, we reviewed clinical trials involving ketogenic interventions in mild cognitive impairment, Alzheimer's disease, and Parkinson's disease reported since 2005. Levels of clinical evidence were systematically reviewed using the American Academy of Neurology criteria for rating therapeutic trials. Results 10 AD, 3 MCI, and 5 PD therapeutic ketogenic trials were identified. Respective grades of clinical evidence were objectively assessed using the American Academy of Neurology criteria for rating therapeutic trials. We found class “B” evidence (probably effective) for cognitive improvement in subjects with mild cognitive impairment and subjects with mild-to-moderate Alzheimer's disease negative for the apolipoprotein ε4 allele (APOε4-). We found class “U” evidence (unproven) for cognitive stabilization in individuals with mild-to-moderate Alzheimer's disease positive for the apolipoprotein ε4 allele (APOε4+). We found class “C” evidence (possibly effective) for improvement of non-motor features and class “U” evidence (unproven) for motor features in individuals with Parkinson's disease. The number of trials in Parkinson's disease is very small with best evidence that acute supplementation holds promise for improving exercise endurance. Conclusions Limitations of the literature to date include the range of ketogenic interventions currently assessed in the literature (i.e., primarily diet or medium-chain triglyceride interventions), with fewer studies using more potent formulations (e.g., exogenous ketone esters). Collectively, the strongest evidence to date exists for cognitive improvement in individuals with mild cognitive impairment and in individuals with mild-to-moderate Alzheimer's disease negative for the apolipoprotein ε4 allele. Larger-scale, pivotal trials are justified in these populations. Further research is required to optimize the utilization of ketogenic interventions in differing clinical contexts and to better characterize the response to therapeutic ketosis in patients who are positive for the apolipoprotein ε4 allele, as modified interventions may be necessary.